A Lexico-Grammatical Analysis of Patriotism, Nationalism, and the Palestinian Cause in Moroccan Football Ultras Discourse - EL Hadifi, Mohammed (International Journal of Language and Literary Studies, 2025)
This study aims to critically examine the discursive construction of themes such as patriotism, nationalism, and the Palestinian cause within the discourse of Moroccan football ultras. Utilizing Norman Fairclough’s three-dimensional approach, the research conducts a lexico-grammatical analysis of 3 selected chants and 20 slogans by Moroccan ultras. The analysis specifically focuses on the two meta-functions proposed by Halliday’s Systemic Functional Linguistics (SFL), which Fairclough incorporates into the initial stage of his three-dimensional model. Adopting a qualitative methodology, this study emphasizes the experiential, relational, and expressive values of the lexico-grammatical features in the ultras’ discourse on patriotism, nationalism, and the Palestinian cause. This paper endeavors to address two key questions: Firstly, how are these themes discursively constructed through lexico-grammatical features? Secondly, how do lexico-grammatical features reveal ultras strategies when discussing these issues? The findings of this study revealed that Moroccan football ultras use diverse ideologically charged lexicon and linguistic techniques such as rewording, over-wording, synonymy, hyponymy, and antonymy to express patriotism and support for the Palestinian cause. They enhance emotional engagement through dysphemism and varying formalities, frequently employing SVO and SVC structures with material and mental processes while avoiding negative sentences. Also, nominalization is used to reinforce their commitment, and active voice highlights the agency of entities. Deictic pronouns and different grammatical modes -declarative, imperative, and interrogative- are employed to establish power relations within the discourse. The findings contribute to broader discussions on the role of sports culture in socio-political activism and lay the groundwork for future studies examining the interplay between sports discourse and socio-political dynamics in different cultural contexts.